Green biosynthesis of bimetallic selenium–gold nanoparticles using Pluchea indica leaves and their biological applications - Aly Khalil, Ahmed Mohamed; Saied, Ebrahim; Mekky, Alsayed E.; Saleh, Ahmed M.; Al Zoubi, Omar Mahmoud; Hashem, Amr H. (Frontiers in Bioengineering and Biotechnology, 2024)
Increasing bacterial resistance and the negative impact of currently used antibacterial agents have produced the need for novel antibacterial agents and anticancer drugs. In this regard, nanotechnology could provide safer and more efficient therapeutic agents. The main methods for nanoparticle production are chemical and physical approaches that are often costly and environmentally unsafe. In the current study, Pluchea indica leaf extract was used for the biosynthesis of bimetallic selenium–gold nanoparticles (Se-Au BNPs) for the first time. Phytochemical examinations revealed that P. indica leaf extract includes 90.25 mg/g dry weight (DW) phenolics, 275.53 mg/g DW flavonoids, and 26.45 mg/g DW tannins. X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier-transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX) techniques were employed to characterize Se-Au BNPs. Based on UV-vis spectra, the absorbance of Se-Au BNPs peaked at 238 and 374 nm. In SEM imaging, Se-Au BNPs emerged as bright particles, and both Au and Se were uniformly distributed throughout the P. indica leaf extract. XRD analysis revealed that the average size of Se-Au BNPs was 45.97 nm. The Se-Au BNPs showed antibacterial properties against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis, with minimum inhibitory concentrations (MICs) of 31.25, 15.62, 31.25, and 3.9 μg/mL, respectively. Surprisingly, a cytotoxicity assay revealed that the IC50 value toward the Wi 38 normal cell line was 116.8 μg/mL, implying that all of the MICs described above could be used safely. More importantly, Se-Au BNPs have shown higher anticancer efficacy against human breast cancer cells (MCF7), with an IC50 value of 13.77 μg/mL. In conclusion, this paper is the first to provide data on the effective utilization of P. indica leaf extract in the biosynthesis of biologically active Se-Au BNPs.